Exploring The Intentions of Social Entrepreneurship: An Empirical Study University Student in Indonesia - Noerhartati, Endang; Soesatyo, Yoyok; Moedjito, Moedjito; Karwanto, Karwanto; Jatiningrum, Citrawati; Tunik Muharlisiani, Lusy (Opción, 2019)
Social entrepreneurship plays a prominent role in cultivating the entrepre- neurship spirit in university students who start up the new ventures. This study investigates the determinant of social entrepreneurship intention on university student related to entrepreneurship education and entrepreneur- ship experience in Indonesia. Through a survey method collected university students as respondent 328 for analyzed. Using statistically Structural Equa- tion Modelling (SEM) method for data analysis, research findings reveal that moral obligation, self-efficacy and social support as determinant factors on social entrepreneurship intention in student university. Moreover, the main finding indicates that entrepreneurship education and entrepreneurship expe- rience will increase the intention to strat up business in the field of social when it mediated with several factors. These findings give a contribution to the uni- versity as one of the contributed institutions in build-up entrepreneurship knowledge for student and also the government in improving the economic growth through the social entrepreneurship in a sustainable way as one of economic improvement.